Kick-starting youth wellbeing and access to mental health care: Efficacy of an integrated model of care within a junior sports development program. (October 2022) - Waters, Allison M.; Sluis, Rachel A.; Usher, Wayne; Farrell, Lara J.; Donovan, Caroline L.; Modecki, Kathryn L.; Zimmer-Gembeck, Melanie J.; Castle, Mike; Hinchey, James
Abstract: One productive avenue for building adolescents' personal strengths and reducing mental health problems is integrating assessment and intervention into organised sports programs. We investigated the efficacy of the RISE program, a rugby league development program for 12- to 15-year-old boys, which integrated a mental health and wellbeing system called Life-Fit-Learning. The Life-Fit System is designed to measure youth's strengths and mental health symptoms and sends mental health feedback to parents, provides group-based workshops, connects youth and parents to online psychoeducation resources, and provides individual telephone follow-up and referral with parents of youth at high-risk for mental health problems. In this study, mental health and wellbeing outcomes were compared in participants who did (RISE, N = 94) and did not (Comparison, N = 82) receive the RISE/Life-Fit-Learning program. RISE players reported their self-satisfaction, grit, gratitude, prosocial behaviour, anxiety, depression, and behavioural problems using the Life-Fit System pre- and post-program. Comparison participants completed measures twice, 6-months apart. Self-satisfaction did not change in RISE participants but declined among comparison participants. In both groups, 26% of players scored in the high-risk range on at least one mental health measure. On mental health measures, high-risk RISE players' depression and behavioural problems improved from pre-to post-program relative to no change among Comparison players. Among participants who were not high-risk, RISE players' anxiety, depression, and behavioural problems did not change whereas Comparison players' behavioural problems increased significantly. Results underscore the value of integrating strengths-based interventions and targeting youth mental health problems within the context of junior sports development programs. Highlights: Examined benefits of youth sports program with an integrated mental health program. Compared to controls, the program mitigated declines in self-satisfaction. The program prevented increases in behavioural problems in healthy participants. The program reduced depression and behavioural problems in high-risk participants.